સાબિત કરો કે $\left|\begin{array}{ccc}a^{2} & b c & a c+c^{2} \\ a^{2}+a b & b^{2} & a c \\ a b & b^{2}+b c & c^{2}\end{array}\right|=4 a^{2} b^{2} c^{2}$

Vedclass pdf generator app on play store
Vedclass iOS app on app store

$\Delta=\left|\begin{array}{ccc}a^{2} & b c & a c+c^{2} \\ a^{2}+a b & b^{2} & a c \\ a b & b^{2}+b c & c^{2}\end{array}\right|$

Taking out common factors $a, b$ and $c$ from $C_{1}, C_{2},$ and $C_{3},$ we have:

$\Delta=a b c\left|\begin{array}{ccc}a & c & a+c \\ a+b & b & a \\ b & b+c & c\end{array}\right|$

Applying $R_{2} \rightarrow R_{2}-R_{1}$ and $R_{3} \rightarrow R_{3}-R_{1},$ we have:

$\Delta=a b c\left|\begin{array}{ccc}a & c & a+c \\ b & b-c & -c \\ b-a & b & -a\end{array}\right|$

Applying $R_{2} \rightarrow R_{2}+R_{1},$ we have:

$\Delta=a b c\left|\begin{array}{ccc}a & c & a+c \\ a+b & b & a \\ b-a & b & -a\end{array}\right|$

Applying $R_{3} \rightarrow R_{3}+R_{2},$ we have:

$\Delta=a b c\left|\begin{array}{ccc}a & c & a+c \\ a+b & b & a \\ 2 b & 2 b & 0\end{array}\right|$

$=2 a b^{2} c\left|\begin{array}{ccc}a & c & a+c \\ a+b & b & a \\ 1 & 1 & 0\end{array}\right|$

Applying $C_{2} \rightarrow C_{2}-C_{1},$ we have:

$\Delta=2 a b^{2} c\left|\begin{array}{ccc}a & c-a & a+c \\ a+b & -a & a \\ 1 & 0 & 0\end{array}\right|$

Expanding along $R_{3},$ we have:

$\Delta=2 a b^{2} c[a(c-a)+a(a+c)]$

$=2 a b^{2} c\left[a c-a^{2}+a^{2}+a c\right]$

$=2 a b^{2} c(2 a c)$

$=4 a^{2} b^{2} c^{2}$

Hence, the given result is proved.

Similar Questions

જો $\mathrm{a, b, c}$ પૈકી પ્રત્યેક બે અસમાન અને પ્રત્યેક ધન હોય, તો સાબિત કરો કે નિશ્ચાયક $\Delta=\left|\begin{array}{lll}a & b & c \\ b & c & a \\ c & a & b\end{array}\right|$ નું મૂલ્ય ઋણ છે.

જો $x, y, z$ ભિન્ન હોય અને $\Delta=\left|\begin{array}{lll}x & x^{2} & 1+x^{2} \\ y & y^{2} & 1+y^{2} \\ z & z^{2} & 1+z^{2}\end{array}\right|=0$ હોય, તો સાબિત કરો કે $1+x y z=0$.

$\left| {\,\begin{array}{*{20}{c}}{x + 1}&{x + 2}&{x + 4}\\{x + 3}&{x + 5}&{x + 8}\\{x + 7}&{x + 10}&{x + 14}\end{array}\,} \right| = $

સાબિત કરો કે, $\Delta=\left|\begin{array}{ccc}
(y+z)^{2} & x y & z x \\
x y & (x+z)^{2} & y z \\
x z & y z & (x+y)^{2}
\end{array}\right|=2 x y z(x+y+z)^{3}$

$2\,\,\left| {\,\begin{array}{*{20}{c}}1&1&1\\a&b&c\\{{a^2} - bc}&{{b^2} - ac}&{{c^2} - ab}\end{array}\,} \right| = $